SENGKETA PERTANAHAN HAK MASYARAKAT ADAT DENGAN HAK GUNA USAHA (HGU) PERKEBUNAN SAWIT DI KALIMANTAN SELATAN - Fat'hul Achmadi Abby (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2017)
The Issues of indigenous has implications broad because it involves the existence of a group of society who call themselves is the law indigenous society, who felt the rightful owners of the land. The conflict of legal issues or potential conflict in the region of cultivation rights titleof oil palm plantations became a serious obstacle in the development of oil palm plantations in South Kalimantan. This study uses research methods of sociology of law (socio-legal research) by using an interdisciplinary approach between aspects of sociological and anthropological research with a normative approach, used the method of qualitative analysis, by deep analysis data and holistic. The consequence of the legal research usessocio-legal paradigm is using normative juridical incorporation method with qualitative sociological methods.Keywords: Conflict of Land, Rights of Indigenous Peoples, Economic Development.